2014
DOI: 10.1186/1472-6882-14-404
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and alternative medicine use amongst Malaysian orthopaedic oncology patients

Abstract: BackgroundAlthough studies have shown that a large proportion of cancer patients use CAM, no study on CAM use amongst orthopaedic oncology patients has been published. Therefore, this study aims to determine the prevalence, characteristics and factors associated with CAM use amongst orthopaedic oncology patients.MethodsAll consecutive consenting patients/parents who presented at the Orthopaedic Oncology Clinic, University Malaya Medical Centre (1st January to 31st December 2013) were interviewed using a struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 38 publications
1
24
0
2
Order By: Relevance
“…Median rates of disclosure differed significantly between LIC/LMIC, UMIC, and HIC, with rates of 21% (± 7%), 32% (± 22%), and 45% (±15%), respectively ( P = .03). Reasons for nondisclosure were reported by eight studies, 45 , 48 , 60 - 65 including four HIC, 45 , 60 , 64 , 65 two UMIC, 61 , 62 and two LIC. 48 , 63 Examples of reasons for nondisclosure included belief that T&CM was nontoxic, 64 fear of the physician’s reaction, 48 , 61 - 63 , 65 belief that the medical staff lacked knowledge of T&CM, 45 , 60 and the physician did not ask.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Median rates of disclosure differed significantly between LIC/LMIC, UMIC, and HIC, with rates of 21% (± 7%), 32% (± 22%), and 45% (±15%), respectively ( P = .03). Reasons for nondisclosure were reported by eight studies, 45 , 48 , 60 - 65 including four HIC, 45 , 60 , 64 , 65 two UMIC, 61 , 62 and two LIC. 48 , 63 Examples of reasons for nondisclosure included belief that T&CM was nontoxic, 64 fear of the physician’s reaction, 48 , 61 - 63 , 65 belief that the medical staff lacked knowledge of T&CM, 45 , 60 and the physician did not ask.…”
Section: Resultsmentioning
confidence: 99%
“… 48 , 63 Examples of reasons for nondisclosure included belief that T&CM was nontoxic, 64 fear of the physician’s reaction, 48 , 61 - 63 , 65 belief that the medical staff lacked knowledge of T&CM, 45 , 60 and the physician did not ask. 45 , 61 …”
Section: Resultsmentioning
confidence: 99%
“…A recent systematic review of surveys in the UK indicated, 51.8 % of the population applied alternative remedies at least once during their lifetime [4]. Among cancer patients the use of CAM grew from 25 % in the 1970s to 49 % in the 2000s [5], and this rate can reach 61 % among orthopaedic cancer patients [6]. In Canada, 27 % of patients waiting for general surgery applied CAM [7], while in the USA the application ratio was 40–67 % [8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated that CAM use increases with serious clinical and health conditions (Reid, Steel et al 2016, Ni, Simile andHardy 2002) and it is exceptionally high among patients with life threatening illnesses such as cancer (Sparber and Wootton 2001) or HIV (Wootton and Sparber 2001). A lot of studies focused on patients with cancer (John, Hershman et al 2016, Dhanoa, Yong et al 2014, Horneber, Bueschel et al 2012, Molassiotis, Fernandez-Ortega et al 2005a, surgery patients (Schieman, Rudmik et al 2009, Norred 2002, Crowe, Fitzpatrick and Jamaluddin 2002, Wang, Peloquin and Kain 2002, Norred, Zamudio and Palmer 2000, cardiac patients (Mandreker 2015) and diabetic patients (Chang, Wallis and Tiralongo 2007). The rate of CAM use by cancer patients was higher among younger patients, females and patients with a higher educational level (Molassiotis, Fernadez-Ortega et al 2005b), however among diabetes patients the main determining factors were age, duration of diabetes, degree of complications and self-monitoring of blood glucose (Chang, Wallis and Tiralongo 2007).…”
Section: Introductionmentioning
confidence: 99%